Paraparesis as a Rare Complication of Dengue Fever Causing Spontaneous Spinal Subarachnoid Haemorrhage - Pradnya Diggikar; Simran Bhullar; Farhanulla Basha; Prashant Gopal (Journal of Clinical and Diagnostic Research, 2022)
A smaller number of confirmed dengue cases worldwide present with neurological symptoms such as headache, seizure, neck stiffness, drowsiness, altered sensorium, behavioural disorders, delirium, cranial nerves palsies, and rarely, spinal cord involvement. This report is about a 54-year-old female patient with dengue, who presented with acute spinal cord compression due to spontaneous spinal Subarachnoid Haemorrhage (SAH). She complained of sudden onset of febrile illness associated with headache, myalgia, retro-orbital pain, and low backache for three days, followed by sudden onset paraplegia three days after the onset of the illness. A haemogram was obtained, which showed a platelet count of 60,000/μL. She had antibodies against dengue NS1 and dengue Immunoglobulin M (IgM), but not against dengue IgG. A Magnetic Resonance Imaging (MRI) spine contrast imaging revealed a spinal SAH from the level of T12 to L1, as well as significant cord compression. An MRI of the brain revealed a SAH in the bilateral parieto-occipital region. She underwent an emergency laminectomy and complete haematoma evacuation. Postsurgical period was uneventful with complete recovery of sensation and weakness. In patients from endemic areas of dengue infection who present with fever and spinal cord involvement a high degree of suspicion of this disease should arise and it should always be investigated further for dengue-related neurological complications.